Kekristenan dan Spiritualitas Online: Cybertheology sebagai Sumbangsih Berteologi di Indonesia Christianity And Online Spirituality: Cybertheology as a Contribution to Theology in Indonesia - Mick Mordekhai Sopacoly; Izak Y.M. Lattu (Gema Teologika, 2020)
The mobilization of information, technology, and social change marked by the presence of cyberspace not only affects the way people think in building relationships with others and themselves but also the process of developing faith and spirituality. Using the methods of qualitative research, literature study, and Focus Group Discussion (FGD), this research finds that in the context of the COVID-19 pandemic, Christian religious patterns are changing drastically, driving all churches to move to virtual reality. The Christian notion of spirituality is also being transformed so that the experience with God is believed to occur not only in the physical space of the church but also in virtual reality. “Clickactivism” forms a new faith community determined by click and spiritual experiences which strength lies in the imagination of communities and individuals. This study concludes that cybertheology is an important contribution in helping Indonesian Christians to have a strong spirituality about God who cannot be confined within time and space.